RELATIONSHIP BETWEEN MACROSOMIA AND GESTATIONAL DIABETES IN BIRTH CONDITIONS (CIPEEX, 2025)
Introduction: Fetal macrosomia, defined as birth weight greater than 4000 grams, may be linked to several factors, such as weight gain during pregnancy and gestational diabetes mellitus (GDM). This condition predisposes to the occurrence of several health complications, both in the newborn and in the mother. This highlights the need for effective prenatal care, consisting of at least six consultations, to reduce health problems and the risk of complications during childbirth. Objective: To analyze the main complications during childbirth and measure the head circumference of babies with macrosomia, with or without gestational diabetes. Methodology: This is a descriptive and quantitative field study conducted through the analysis of medical records at the Children and Adolescents Outpatient Clinic (ACA), using the measurements used by the Ministry of Health. The data collected were compiled into an Excel table and analyzed. Results: A total of 520 medical records were analyzed, of which only 13 were included, and 2 showed the presence of GDM. Among the parameters considered, changes were observed in the medical records with GDM, with lower APGAR scores, higher head circumference z-scores, and the presence of complications during delivery. Conclusion: There is a relationship between macrosomia with the presence of DMG and changes in birth conditions. However, due to the small sample size, further research on the subject is necessary.
Keywords: fetal macrosomia; gestational diabetes; pregnant women; newborns